2004
DOI: 10.1002/ps.858
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring and characterization of Magnaporthe grisea isolates with decreased sensitivity to scytalone dehydratase inhibitors

Abstract: Rice blast fungus isolates were collected in Kyushu to investigate resistance to scytalone dehydratase inhibitors of melanin biosynthesis (MBI-D). In 2001, failure of control of rice blast was reported in the Saga prefecture, where MBI-Ds have been used since 1998. At that time, the distribution of resistant isolates was mainly limited to that area. However, in 2002, resistant isolates were detected in all prefectures of Kyushu. DNA fingerprinting analysis showed that the mutation causing resistance to MBI-Ds … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 12 publications
0
25
0
Order By: Relevance
“…demonstrated that 1 and 10 µg a.i./mL of carpropamid did not have efficacy in control-resistant isolates of M. oryzae in the greenhouse. 25) Although several reports demonstrated that the carpropamid-resistant isolates of M. oryzae had been detected in fields, 24,25,27,39) the M. oryzae isolates from Taiwan still showed sensitivity to carpropamid. In addition, certain researchers indicated that using mycelial melanization also could be helpful to compare the sensitivity of M. oryzae isolates to tricyclazole 28) and carpropamid.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…demonstrated that 1 and 10 µg a.i./mL of carpropamid did not have efficacy in control-resistant isolates of M. oryzae in the greenhouse. 25) Although several reports demonstrated that the carpropamid-resistant isolates of M. oryzae had been detected in fields, 24,25,27,39) the M. oryzae isolates from Taiwan still showed sensitivity to carpropamid. In addition, certain researchers indicated that using mycelial melanization also could be helpful to compare the sensitivity of M. oryzae isolates to tricyclazole 28) and carpropamid.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, certain researchers indicated that using mycelial melanization also could be helpful to compare the sensitivity of M. oryzae isolates to tricyclazole 28) and carpropamid. 24,40) Zhang et al (2006) used a minimum inhibition concentration of mycelial melanization (MIC-H) to detect the sensitivity of M. oryzae isolates from China to tricyclazole. 28) However, the MIC-H was considered not stable to examine the sensitivity of M. oryzae isolates to tricyclazole compared with MICAM.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…8,9) Studies on the mechanism of resistance and characterization of mutant STD proved that a single-point mutation resulted in a one-amino acid substitution (valine [GTG] 75 to methionine [ATG]: V75M) in STD. 10,11) Recently, new STD-inhibitors such as diclocymet 12) and fenoxanil 13) have been developed and registered as anti-blast chemi-cals in Japan.…”
Section: Reviewmentioning
confidence: 99%
“…Isolates resistant to carpropamid were first reported in 2001 in Saga Prefecture, 4) and these isolates showed cross-resistances to other MBI-D fungicides. A single-point mutation in the SH gene (GenBank Accession Number AB004741), which causes the substitution of one amino acid in SH (valine 75 to methionine: V75M; R-mutation), was found in the carpropamid-resistant isolates.…”
mentioning
confidence: 99%